SIFAT FUNGSIONAL DAN SIFAT PASTA PATI SAGU BANGKA - MERYNDA INDRIYANI SYAFUTRI (Jurnal Sagu, 2015)
The aims of this research was to identify the functional and pasta properties of Bangka sago starch. Bangkasago starch used in this research were obtained from Bangka Belitung province. This research was descriptive.Data presented in tabulated form. The results showed that functional properties of Bangka sago starch were23.75 to 25.10% of solubility index, 20 to 22% of swelling power, 79.40 to 80.77% of total starch, 33.12 to42.24% of amylose content, 57.76 to 66.88% of amylopectin content, and the granular form was oval. Bangkasago starch had final viscosity value 3188.5 to 3295.5 BU and pasting temperature 73.34 to 73.36 ° C.Key words : Bangka sago starch, functional properties, pasta properties